Spiritual mindfulness therapy: An intervention to reduce depression symptoms - Solichah, Novia; Hidayah, Rifa; Zakiyah, Ermita; Pandya, M. Fikran; Ogbuabor, Shulamite Ebere (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Depression has become a critical mental health issue, especially among college students, with increasing prevalence worldwide. According to the World Health Organization (WHO), approximately 322 million people globally suffer from the condition, with a prevalence rate of around 3.7% in Indonesia. This research examines the effectiveness of spiritual mindfulness therapy in reducing depression symptoms among university students. The study involved 28 Malang students aged 18 to 22 who participated voluntarily. The research approach was based on quantitative methods, with an experimental Solomon Four-Group design, in which the participants were divided into four groups: two who received treatment and two who served as controls. Spiritual mindfulness therapy was administered through both individual and group sessions, with depression levels measured using the PHQ-9 instrument before and after the 8-session intervention, using pre-test and post-test assessments. The results show a significant reduction in depression symptoms, differing between the groups (F = 18.547, p < .001), with the analysis indicating a significant improvement in the treatment groups. The effect sizes ranged from d = 2.75 to d = 3.33, indicating a high therapeutic impact. The research implies that spiritual mindfulness therapy can effectively alleviate depressive symptoms in students, providing a promising intervention for mental health support in educational settings.